How Do Physical Therapists and Athletic Trainers Maintain Their Physical Fitness? A Descriptive Survey Study - Scott W Cheatham; Brian Sutton; Tony Ambler-Wright; Connor J Cheatham; Christopher M Ludwig (International Journal of Sports Physical Therapy)
# Background